Search of Cryoprotective Medium for Vitrification of Fetal Fibroblast-Like Cell Suspension - Gorokhova, N. A.; Petrenko, Yu. A.; Petrenko, A. Yu. (Problems of Cryobiology and Cryomedicine, 2007)
The paper covers the search of cryoprotective medium composition, allowing to avoid the crystal formation during rapid freezethawing in standard cryovials, as well as the effect of exposure and freezing-thawing in the media on survival of fetal fibroblast-like cells. The composition of vitrification media included dimethyl sulfoxide (DMSO), ethylene glycol (EG), 1,2-propane diol (1,2-PD) and sucrose. The applicability of the media was visually assesed by presence or absence of crystal formation during freeze-thawing, and two media were selected for vitrification of cell suspensions: DEPS-1 (10% of DMSO, 20% of EG, 20% of 1,2-PD and 0,5 M of sucrose) and DEPS-2 (10% of DMSO, 15% of EG, 15% of 1,2-PD and 1 M of sucrose). Exposure to DEPS-1 and DEPS-2 led to decrease in cell survival and ability to adhere to plastic. After freeze-thawing in DEPS-2 the cell survival decreased by 30% comparing to the values before freezing, and in DEPS-1 no changes were observed and the cells proliferate in culture. Thus the possibility of fetal fibroblast-like cell suspension to be vitrified in multicomponent cryoprotective media during rapid freezing in standard plastic cryovials was shown.